Efeito do óleo essencial da Lavanda (Lavandula angustifolia Mill) sobre a resposta inflamatória aguda - Cardia, Gabriel Fernando Esteves (2016)
This study evaluated the anti-inflammatory activity of LEO administered orally and topically. The inflammatory process is a complex response of vascularized tissue to irritant stimuli by activating and release of various inflammatory mediators aiming to repair tissue damage. Natural products and their essential oils have been widely used as an alternative to the treatment of various inflammatory diseases and the development of new therapeutic strategies, since they have low toxicity and few adverse effects. The essential oil of lavender (LEO) shows various pharmacological effects such as anticonvulsant, anxiolytic, antioxidant, anticholinesterase, antimicrobial and antifungal activities. The objective of this study was to investigate the LEO activity in experimental models of acute inflammation using ear edema models induced by croton oil and paw edema induced by carrageenan and dextran. Furthermore, it was determined the activity of the enzyme myeloperoxidase and nitric oxide concentration. It was determined the constituents of LEO and its cytotoxic effects and chemoattractant. The results showed that the main constituents of LEO are 1,8-cineol, borneol and camphor. LEO an anti-inflammatory activity in vivo can reduce the infiltration of neutrophils into the inflamed tissue, both in the topical treatment as orally, capable and reduce edema and activity of the enzyme myeloperoxidase (MPO) in the ear edema and paw edema induced by carrageenan and dextran. Treatment with LEO also reduced nitric oxide (NO) production. The LEO showed no chemoattractant have the potential for any concentration tested in the in vitro chemotaxis model, in low concentrations (0.5, 1, 3, 10/ml), showed to be cytotoxic. These effects may be related to the inhibition of various inflammatory and/or allergic mediators, which were primarily concerned with histamine and partially with NO.